Escribir la norma : problemas de recepción, acatamiento y publicación de los documentos reales en las Indias durante el Antiguo Régimen - Margarita Gómez Gómez (Les Cahiers de Framespa)
The present study intends to reflect on the effects that distance could have on the implementation and enforcement of laws in the Indies. To achieve this, this article will analyze the practices and methods used in those territories from two perspectives: first, the correct reception, compliance and publication of the royal documents; and second, the omission and failure to comply with said royal orders. This piece will also study the consequences of these bad practices, paying attention to the sanctions and, above all, to the remedies that the monarchy adopted to try to alleviate the undeniable effects that, as will be seen, distance had in the implementation of laws in the Indies and in their publication.